Vegetación del Valle La Invernada (Reserva Privada Don Carmelo) en el centro oeste de la Provincia de San Juan (Argentina) - Ripoll Busso, Yanina Elizabeth (2019)
Vegetation of the La Invernada valley (Don Carmelo Private Reserve) in the central-west of San Juan province (Argentina). In this paper, the vegetation of La Invernada valley, located in the Andean Precordillera of San Juan province, was analyzed. A total of 146 floristic releves were made, and environmental variables as slope, geomorphologic unit, altitude, plant cover were recorded, and physic-chemical analyses of soils were carried out. The biologic and chorologic spectra for each community were performed. Obtained data were analyzed using multivariate methods. In total, 143 vascular plant species were recorded, and ten plant communities determined. Dominant life forms were chamaephytes and hemicriptophytes. Chorologically the studied area belongs to the Cuyano District of the phytogeographical province of Puna, while below 2600 m a.s.l. elements of Cardonal and Monte are found.